2014
DOI: 10.1186/1471-2458-14-s3-s5
|View full text |Cite
|
Sign up to set email alerts
|

Fitness level and body composition indices: cross-sectional study among Malaysian adolescent

Abstract: Background: The importance of fitness level on the well-being of children and adolescent has long been recognised. The aim of this study was to investigate the fitness level of school-going Malaysian adolescent, and its association with body composition indices. Methods: 1071 healthy secondary school students participated in the fitness assessment for the Malaysian Health and Adolescents Longitudinal Research Team (MyHEART) study. Body composition indices such as body mass index for age, waist circumference an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 56 publications
1
13
0
1
Order By: Relevance
“…This fact could be attributed to the beneficial effect of increased meal frequency on appetite regulation, on postprandial metabolic and endocrine responses, as well as on non-excise physical activity, although results of the scientific literature on this topic remain largely controversial and are not so far supported by interventional studies [59][60][61]. Our findings also confirm previous results that physical activity level, cardiorespiratory fitness level and time spent in sedentary activities are associated with the presence of childhood obesity and central obesity [25][26][27][28][29][30][31]. It is noteworthy that in our study, sedentariness was a stronger predictor of childhood central obesity compared to physical activity level, suggesting that besides a lack of physical activity it could also reflect other unhealthy habits.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This fact could be attributed to the beneficial effect of increased meal frequency on appetite regulation, on postprandial metabolic and endocrine responses, as well as on non-excise physical activity, although results of the scientific literature on this topic remain largely controversial and are not so far supported by interventional studies [59][60][61]. Our findings also confirm previous results that physical activity level, cardiorespiratory fitness level and time spent in sedentary activities are associated with the presence of childhood obesity and central obesity [25][26][27][28][29][30][31]. It is noteworthy that in our study, sedentariness was a stronger predictor of childhood central obesity compared to physical activity level, suggesting that besides a lack of physical activity it could also reflect other unhealthy habits.…”
Section: Discussionsupporting
confidence: 92%
“…television watching, computer use, etc.) have been inversely associated with the likelihood of central obesity in children and adolescents [25][26][27][28][29][30][31]. However, the association between lifestyle habits and the presence of central obesity in childhood remains vague, given that most of the available data come from cross-sectional studies confined to particular geographical areas and with relatively small sample sizes [17-19, 21, 24-26, 29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, reverse correlations between PA level and indicators of obesity (e.g., BMI, waist circumference [WC], and body-fat percentage [BF %]) among Malaysian adolescents suggested that the risk of obesity was greater among those who are physically inactive 7 . Therefore, immediate assessment of trends in PA level, BC indices, and lipid profiles seems vital in preventing the future negative health consequences 9 .…”
mentioning
confidence: 99%
“…Hooten et al used multiple variable linear regression for the relation between knee joint kinetics and pressure pain threshold [20]. Multiple regression was used for predictive factors such as physical composition to physical fitness standards [21]. Gorman et al used logistic regression [22], while Duncan et al randomly divided groups into the following quantile ranks according to cardiorespiratory fitness: lower, middle, and high groups, representing the lower twentieth, twentieth to fifty-ninth, and over sixtieth, respectively [23].…”
Section: Roc and Non-roc-used Methods Or Analysis Of Criterion-referementioning
confidence: 99%